SAFETY MANAGEMENT PRACTICES ADOPTED BY PRINCIPALS FOR EFFECTIVE ADMINISTRATION OF PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2024)
The study investigated safety management practices adopted by principals for effective administration of public secondary schools in Anambra State. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. Descriptive survey research design was adopted for the study. The population of the study comprised 7,293 respondents made up of 266 principals and 7,027 teachers in the 266 public secondary schools in Anambra State. The sample for this study consisted of 809 respondents made up of 106 principals and 703 teachers drawn using proportionate stratified random sampling technique. A researcher-developed instrument titled ‘‘Safety Management Practices for Effective Administration Questionnaire (SMPEAQ).’’ was used for data collection. The instrument was validated by three experts of which two were from the Department of Educational Management and Policy, and one in Measurement and Evaluation Unit in the Department of Educational Foundations, all from Faculty of Education, Nnamdi Azikiwe University, Awka. Cronbach alpha method was used for a test of internal consistency of the instrument which yielded reliability coefficients 0.81 and 0.80 for Clusters A and B respectively. Mean and standard deviation were used to answer the research questions, while t-test was used to test the null hypotheses at 0.05 level of significance. The findings of the study revealed among others that safety communication and feedback practices as well as safety rules and procedures practices are adopted by principals for effective administration of public secondary schools in Anambra State.  It was also found that, there is no significant difference in the mean ratings of principals and teachers on all dimensions of safety management practices adopted by principals for effective administration of public secondary schools in Anambra State. Based on the findings, it was recommended among others that principals should organize termly interactive session with members of staff to use platform to facilitate safety communication and feedback practices for school effective administration.
Keywords: Safety Management, Principals, Effective, School Administration, Communication Feedback, Rules, Procedures